2009
DOI: 10.1016/j.bandc.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and emotion recognition in semantic dementia: A case report

Abstract: a b s t r a c tRecent studies have demonstrated that patients suffering from frontotemporal lobar degeneration (FTLD) show impairments in empathy and emotional processing. In this study, we examined two different aspects of these abilities in a patient with semantic dementia (SD), a variant of FTLD. The first aspect was the assessment of the cognitive and emotional components of empathy through the Interpersonal Reactivity Index. The second was the naming and comprehension of emotions using the Ekman 60 Faces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 41 publications
4
24
0
2
Order By: Relevance
“…In prior work, we demonstrated that experimentally decreasing the accessibility of emotion words’ semantic meaning, using a procedure called “semantic satiation”(Tian & Huber, 2010), reduces the accuracy with which participants produce the presumed universal pattern of emotion perception (Lindquist et al, 2006a) because words help to shape the underlying perceptual representation of those faces (Gendron et al, 2012). Our current findings are consistent with research on patients with semantic deficits due to progressive neurodegeneration (i.e., semantic dementia) or brain injury (i.e., semantic aphasia), who do not perceive emotions in scowls, pouts, smiles and so on (Calabria, Cotelli, Adenzato, Zanetti, & Miniussi, 2009; Roberson, Davidoff, & Braisby, 1999). Even research in young children points to the importance of emotion words in emotion perception, because the presumed universal pattern of emotion perception emerges in young children as they acquire conceptual categories, anchored by words, for emotions (Widen & Russell, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In prior work, we demonstrated that experimentally decreasing the accessibility of emotion words’ semantic meaning, using a procedure called “semantic satiation”(Tian & Huber, 2010), reduces the accuracy with which participants produce the presumed universal pattern of emotion perception (Lindquist et al, 2006a) because words help to shape the underlying perceptual representation of those faces (Gendron et al, 2012). Our current findings are consistent with research on patients with semantic deficits due to progressive neurodegeneration (i.e., semantic dementia) or brain injury (i.e., semantic aphasia), who do not perceive emotions in scowls, pouts, smiles and so on (Calabria, Cotelli, Adenzato, Zanetti, & Miniussi, 2009; Roberson, Davidoff, & Braisby, 1999). Even research in young children points to the importance of emotion words in emotion perception, because the presumed universal pattern of emotion perception emerges in young children as they acquire conceptual categories, anchored by words, for emotions (Widen & Russell, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In a large-scale VBM study on neurodegenerative disorders [146], a similar neuroanatomical association with PT scores was found in the subgroup of patients affected by Semantic Dementia (SD). The correlation that we found between scores in PT and verbal comprehension deficits was also previously documented in a group of SD patients [147,148]. These combined results suggest that reduced cognitive empathy may be associated with deficits in semantic memory and linguistic comprehension, rather than empathic mechanisms of simulation [149].…”
Section: Empathy and Interpersonal Reactivity Measurements In MCI Indsupporting
confidence: 83%
“…However, if these factors are not present in the IRI, the measurement of cognitive and affective empathy in this study is likely not valid and any rehabilitation efforts inefficient and difficult to evaluate. The same holds true for other psychiatric illnesses that have been tied to empathy such as depression, sociopathy, and autism spectrum disorders (Bock & Hosser, 2014;Cusi et al, 2011;Samson, Huber, & Gross, 2012;Thoma et al, 2011), as well as studies attempting to link these empathic subprocesses to distinct brain systems (Calabria et al, 2009;Dziobek et al, 2011;Hooker et al, 2010;Shamay-Tsoory et al, 2004;Shamay-Tsoory et al, 2009). Because of the importance of empathy for several aspects of social life, reevaluating the use of the two-factor approach to the IRI as a valid measure of cognitive and affective empathy is critical to advance our understanding of this valuable psychological construct, as well as support the use of the IRI as it was originally intended and the development of behavioral and self-report measures that can accurately capture cognitive and affective empathy.…”
Section: Discussionmentioning
confidence: 91%